PENGGUNAAN INDEX of BIOTIC INTEGRITY (IBI) UNTUK MENILAI KUALITAS LINGKUNGAN PERAIRAN - Sukimin, Sutrisno (Jurnal Teknologi Lingkungan, 2007)
Historically, the health of aquatic systems was monitored primarily through chemical means. However, chemical monitoring provides only a "snapshot" of conditions at the time of sampling and may fail to detect acute pollution events (e.g. runoff from heavy rain, spills), non-chemical pollution (e.g. habitat alteration) and non-point source pollution. In order to address the shortcomings of chemical monitoring, the biological monitoring could be used and more accurately reflect the health of ecosystem. Biological monitoring is based on the premise that biological communities are shaped by the long-term conditions of their environment and more accurately reflect the health of an ecosystem.